Los depredadores de tetranychus tumidus banks en Cuba - Perez, R.P.=700 1 Almaguel, L.; Caceres, I.; Feito, E.; De la Torre, E.
(Es, En)
Ilus., 13 ref.
Keywords: TETRANYCHUS TUMIDUS; PHYTOSEIDOS MACROPILIS; AMBLYSEIUS; CERYSOPA; SCOLOTHRIPS; STETHORUS; DEPREDADORES; CUBA